Biological changes after dental panoramic exposure: conventional versus digital - Rurie Ratna Shantiningsih; Silviana Farrah Diba (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Dental digital radiography is more practical and requires fewer doses of radiation than conventional radiography. Because ionizing radiation has a biological effect on exposed tissue, concerns regarding its stochastic effect merit greater attention. In a previous study, it was found that biological changes and increases in the micronucleus occurred after conventional panoramic exposure to gingival crevicular fluid (GCF). Purpose: The purpose of this study is to investigate the difference in biological effects after digital panoramic exposure compared with conventional exposure. Methods: Twenty subjects were classified into two groups according to the radiographic technique employed. The techniques consisted of ten subjects undergoing digital panoramic radiograph exposure and ten others being subjected to conventional exposure. GCF calculated in mm3 was collected by applying paper strips to the anterior maxillary labial gingival sulcus for one minute prior to and ten minutes after exposure. A micronucleus was obtained from a gingival smear on the same quadrant ten days after panoramic exposure. Results: There was a significant difference in the number of micronuclei between conventional and digital panoramic radiographs both before and after exposure (p=0.000). In contrast, increased GCF volume was not statistically significant (p=0.506) before or after digital panoramic exposure, while the significant difference of conventional panoramic exposure was p=0.017. Conclusion: Digital panoramic radiograph exposure induced a biological change only in terms of an increase in the number of micronuclei but not in the volume of GCF.